EP.WE.264How much are we spending on Botulinum Toxin A injections for functional Upper Gastrointestinal conditions?. (28th October 2021) - Afzal, Zeeshan; Sreedharan, Loveena; Hasan, Ibtisam; Corbett, Gareth; Hardwick, Richard
Abstract: A number of Oesophagogastric (OG) conditions such as Achalasia, Gastroparesis, Oesophageal dysmotility (OD) and Pyloric dysfunction (PD) can be treated with Botulinum Toxin A (BTxA). The aim of our study was to assess the use and costs of Botulinum Toxin A endotherapy within a tertiary Oesophagogastric unit. We performed a retrospective analysis of data collected over a 2-year period at a tertiary Oesophagogastric unit from November 2015 to November 2017. We found 68 eligible patients with Achalasia, Gastroparesis, Oesophageal dysmotility, Pyloric dysfunction. The median number of treatment sessions were Achalasia 2 (1-3), Gastroparesis: 2 (1-9), Oesophageal dysmotility: 1 (1-5) and Pyloric dysfunction: 1.5 (1-3). The mean number of units of BTxA used per procedure (Unit) were Achalasia 200, Gastroparesis 170, Oesophageal dysmotility 190 and Pyloric dysfunction 270. A total of 126 vials containing 63000 units (£19530) were opened. 25520 units were used, and 37480 2. Vbn vcfunits were wasted (£11618) over 2 years. On average, 67% of each vial of Dysport was wasted. The local annual wastage was £5810 per year, which roughly equates to a national wastage cost of £348, 600 per year for these 4 OG conditions alone (assuming we serve population of around 1 million people and therefore multiplying by 60). An option for cost saving would be to consider using smaller volume vials to reduce wastage. We would recommend that guidelines are produced in order to standardise the optimal dose required and the vial sizes to stock for treatment of these conditions and avoid unnecessary expenditure.